2011
DOI: 10.1029/2010pa002111
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying export production in the Southern Ocean: Implications for the Baxs proxy

Abstract: The water column and sedimentary Baxs distribution around the Crozet Plateau is used to decipher the controls and timing of barite formation and to evaluate how export production signals are recorded in sediments underlying a region of natural Fe fertilization within the Fe limited Southern Ocean. Export production estimated from preserved, vertical sedimentary Baxs accumulation rates are compared with published export fluxes assessed from an integrated study of the biological carbon pump to determine the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 106 publications
2
14
0
Order By: Relevance
“…Opal is composed mainly of the frustules of diatoms, phytoplankton that produce much of the carbon exported from the surface ocean (Boyd & Trull, ; Buesseler et al, ), while xsBa (barite, BaSO 4 ) microcrystals are produced primarily in the thermocline within decomposing organic aggregates (e.g., Ganeshram et al, ). Barite is perhaps the best calibrated and most reliable inorganic indicator for past changes in the flux of organic carbon to the deep sea in pelagic environments (Hernandez‐Sanchez et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Opal is composed mainly of the frustules of diatoms, phytoplankton that produce much of the carbon exported from the surface ocean (Boyd & Trull, ; Buesseler et al, ), while xsBa (barite, BaSO 4 ) microcrystals are produced primarily in the thermocline within decomposing organic aggregates (e.g., Ganeshram et al, ). Barite is perhaps the best calibrated and most reliable inorganic indicator for past changes in the flux of organic carbon to the deep sea in pelagic environments (Hernandez‐Sanchez et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, organic carbon is sensitive to oxygen concentrations in bottom and pore waters (e.g., Arndt et al, 2013;Ganeshram et al, 1999;Hedges et al, 1999), but its preservation is additionally affected by benthic activity and bioturbation (Canfield, 1994;Hartnett et al, 1998), host sediment composition (Keil et al, 1994;Keil & Hedges, 1993), and sedimentation rates (Müller & Suess, 1979). Excess barium, primarily in the form of barite (Dymond et al, 1992;Hernandez-Sanchez et al, 2011), is sensitive to sedimentary redox conditions (Dymond et al, 1992;Eagle et al, 2003;Hernandez-Sanchez et al, 2011;McManus et al, 1994McManus et al, , 1998Paytan & Griffith, 2007;Torres et al, 1996;van Os et al, 1991), such that under substantial sulfate reduction, barite dissolves and releases barium back to the pore waters, reducing or even eliminating any productivity record in that sedimentary proxy (Dickens, 2001;Dymond et al, 1992;Schenau et al, 2001). Dissolution of opal is omnipresent on the seafloor, since seawater is always undersaturated in dissolved silica, and thermodynamically, opal will dissolve until the pore water concentrations of silica reach equilibrium (Archer et al, 1993;Ragueneau et al, 2000).…”
Section: 1029/2018pa003363mentioning
confidence: 99%
“…Previous studies have reported good correlations between Ba bio (or barite) and the flux of either organic carbon or of biogenic opal [e.g., Dehairs et al, 1980;Bishop, 1988;Dymond et al, 1992;François et al, 1995;Dymond and Collier, 1996;Paytan and Griffith, 2007]. Some controversy exists about the relationship of barite and Ba bio [Eagle et al, 2003;Robin et al, 2003], but recent studies have confirmed that Ba bio consists mainly of barite [e.g., Hernandez-Sanchez et al, 2011]. Barite is formed in the oxic microenvironments of decaying organic-rich particulate aggregates within the upper thermocline [e.g., Dehairs et al, 1980;Bishop, 1988;Dymond et al, 1992;François et al, 1995;Dymond and Collier, 1996;Paytan and Griffith, 2007].…”
Section: Application Of Biogenic Barium Fluxes As a Paleoproductivitymentioning
confidence: 99%